2022
DOI: 10.1149/10701.10631ecst
|View full text |Cite
|
Sign up to set email alerts
|

General Aspects, Applications, and Recent Advancements of 1, 2-Disubstituted Benzimidazole Mannich Bases: A Privileged Scaffold

Abstract: Chemistry of heterocyclic compounds performs foremost part in synthesis of various pharmacological active compounds. Existence of benzimidazole core in innumerable group of medicinal agents, such as anti-inflammatory, anticancer, antiviral, antimicrobial, antihypertensive, and immune-modulators, contributed them to be essential announcer for growth of new pharmacological active agents. Mannich synthesis is significantly used in organic chemistry. This reaction is useful for synthesizing many bioactive drug mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…[14] Incorporation of basic functional group via Mannich reaction renders the Mannich product very reactive and pharmacologically significant. Various reports from the literature revealed that Mannich bases possess antimicrobial, [15] anti-inflammatory, [16] analgesic, [17] anti-convulsant [18] activities etc.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Incorporation of basic functional group via Mannich reaction renders the Mannich product very reactive and pharmacologically significant. Various reports from the literature revealed that Mannich bases possess antimicrobial, [15] anti-inflammatory, [16] analgesic, [17] anti-convulsant [18] activities etc.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are known for their antiviral [10,11], anti-inflammatory [12][13][14], anticancer [15][16][17], antimicrobial [18][19][20], anti-HIV [21], anti-diabetes [22,23], and anticonvulsant [24] activities. Furthermore, benzimidazole compounds possess biological properties, including antioxidant activities [25][26][27].…”
Section: Introductionmentioning
confidence: 99%